2014
DOI: 10.5296/ijhrs.v4i3.5875
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Rewards & Corporate Social Responsibility (CSR) On Employee Motivation

Abstract: After a long period of research on this topic, motivating employees and retaining them is still a threatening challenge for organizations. The study aims to analyze impact of rewards and corporate social responsibility (CSR) on employee"s motivation in Pakistan. This study specifically examines the relationship between intrinsic rewards, extrinsic rewards, internal International Journal of Human Resource Studies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Extrinsic motivation in this study was assessed from employees' concern for evaluation, recognition/rewards, competition/competition, money/incentives and orders from others. In line with the research of Khan et al (2014), Lin (2011), Saeed and Asghar (2012), Remi (2011), Parker et al (2012), Bear et. al.…”
Section: Predictors: (Constant) Training Extrinsic Motivationsupporting
confidence: 75%
See 1 more Smart Citation
“…Extrinsic motivation in this study was assessed from employees' concern for evaluation, recognition/rewards, competition/competition, money/incentives and orders from others. In line with the research of Khan et al (2014), Lin (2011), Saeed and Asghar (2012), Remi (2011), Parker et al (2012), Bear et. al.…”
Section: Predictors: (Constant) Training Extrinsic Motivationsupporting
confidence: 75%
“…The higher benefit that might be obtained by the employees like salary, incentives, and job promotion, the better their work performance. Extrinsic motivation play a big role in accommodating the primary needs of employees (Khan et al, 2014). Extrinsic motivation improves employees performance through good working conditions, policies, security, and relationships between employees (Emeka et al, 2015).…”
Section: Extrinsic Motivation and Individual Work Performance Of The ...mentioning
confidence: 99%
“…However, there is research showing conflicting results. For example, Khan et al [73] found no influence from internal CSR on intrinsic motivation but found a positive and significant influence between external CSR and intrinsic motivation. Our research measured employees' CSR perception, rather than actual CSR practices, so the difference might have resulted in the conflict.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the study CEMJ 31,4 including 274 Lithuanian employees found a positive and significant relationship between CSR and employees' intrinsic motivation (Skudiene & Auruskeviciene, 2022). Studies in South Korea (Kim, Rhou, Uysal, & Kwon, 2017) and India (Khan, Latif, Jalal, & Rizwan, 2014;Nazir, Ul, & Rahman, 2021) yielded similar results.…”
Section: Discussionmentioning
confidence: 85%